Additive value of three-dimensional power Doppler in differentiation between uterine myomas and localized adenomyomas. Issue 1 (February 2016) - ElGhamry, Nevine; Al-Ini, Kasr
Abstract : Objective: The aim of this study was to evaluate the value of three-dimensional (3D) power Doppler ultrasonography in differentiating between adenomyosis and uterine leiomyoma. Design: This was a cross-sectional study. Setting: The study was conducted in Kasr El-Ainy Hospital. Patients and methods: This study was conducted on 60 patients between 20 and 60 years of age, who were previously diagnosed on 2D ultrasonography as having adenomyosis and/or leiomyoma. 3D power Doppler ultrasound was performed before surgery (myomectomy or hysterectomy). The examination evaluated vascular location (location), vascular index, flow index, and vascular-flow index. Postoperative histopathological examination was carried out to confirm the diagnosis. Results: Patients with uterine leiomyoma had significantly higher vascular index ( P =0.005), flow index ( P <0.01), and vascular-flow index ( P =0.004) levels than did patients with adenomyosis. A significant difference in vascular location was also noted between cases of uterine leiomyoma and adenomyosis ( P ⩽0.001). Conclusion: 3D power Doppler ultrasonography could be used to more effectively differentiate between uterine adenomyosis and leiomyoma.